Assessment of Job Stress of Clinical Pharmacists in Ho Chi Minh City, Vietnam: A Cross-Sectional Study - Nguyen-Thi, Hai-Yen; Do-Tran, Minh-Thu; Nguyen-Ngoc, Thuy-Tram; Do, Dung Van; Pham, Luyen Dinh; Le, Nguyen Dang Tu (Frontiers in Psychology, 2021)
Introduction: The official implementation of clinical pharmacy into healthcare practice in Vietnam is relatively late, resulting in various stressors. The aim of this study is to evaluate job stress level and suggest solutions to relieve stress for clinical pharmacists (CPs). Methods: A cross-sectional study was conducted on CPs in 128 hospitals in HCMC. Job stress questions were derived from Healthcare Profession Stress Inventory (HPSI). Results: 197 CPs participated, giving a response rate of 82.4%. Participants have moderate job stress with overall mean stress score of 1.5 (0.4) and stress rate of 52.8%. More than 90.0% of reported stress CPs experience moderate level of stress. Statistical analysis indicated that the sample size was adequate and the HPSI was valid and reliable. Patient care responsibility was the main stressor, especially in public hospitals, followed by job conflicts (short-staffing, work overload). Lack of experience, low income and inability to participate clinical ward rounds with clinical care team cause significant stress to CPs regarding job recognition and job uncertainty during treatment and consulting. More practice-oriented training programs in bachelor curricula and clinical practice should be applied to help CPs gain more experience, self-confidence and diminish job stress. Conclusion: CPs in HCMC have moderate stress and most experienced low level of job stress. More practice-oriented training programs in clinical practice and in bachelor curricula should be prioritized to lessen stress for CPs.